Parents' and teachers' views of the promotion of healthy eating in Australian primary schools - Gozde Aydin; Claire Margerison; Anthony Worsley; Alison Booth (BMC, 2021)
Abstract Background Primary schools have long been identified as appropriate settings for improving the healthy eating behaviours of children and helping them develop food skills. This qualitative study explored the views of Australian primary school parents and teachers about schools' strengths and weaknesses in promoting healthy eating and equipping children with food skills. Methods Nineteen parents and 17 teachers from Victoria participated in semi-structured interviews. Audio recordings were transcribed and underwent thematic analysis using Nvivo. Results This study demonstrated that parents and teachers believed that several facilitators helped promote children's healthy eating. These included food and nutrition education (FNE) programs, the community-based nature of schools, and teacher role modelling and the authority schools possess over children. Time scarcity, lack of teacher expertise, lack of leadership and funding were reported as barriers. School food environments such as canteens, lunch orders, fundraising events and school fairs were identified as both weaknesses and strengths by parents and teachers, which indicated inconsistent implementation of school nutrition policies across schools. Conclusions Australian primary schools demonstrate some useful efforts to promote healthy eating among children. However, there are numerous facilitators and barriers which impact on the promotion of healthy eating. These factors need to be addressed in order to develop healthy eating habits further among elementary students. These results provide directions for policymakers and school managers, as they point to the areas that need to be improved to assist the design of schools that better promote healthy eating among children.